1979
DOI: 10.1159/000145154
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of the metopic suture in adult Indian crania

Abstract: 1,276 adult Indian skulls were examined for the incidence of the metopic suture. It was observed that metopism was present in 2.66% of the skulls and metopic sutures were present in 38.17% of the skulls. The metopic suture was present in the lower part of the frontal bone in various shapes in 35.27% of cases. The incidence in the upper, upper middle and lower middle parts of the frontal bone is 0.8% in each type. Besides the above-mentioned findings a peculiar type of shape was seen in 0.63 (inverted y) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 1 publication
(1 reference statement)
5
18
0
7
Order By: Relevance
“…Incidence of persistence metopic sutures in Indian populations were observed by previous authors as follows, B. V. Murlimanju, 52 (64.1%), 4 Hussain Saheb S 3.2%, 5 Agarwal 2.66%, 6 Das 3.31%, 7 Jit & Shah 5%. 8 Incidence among other population were , Breathnach et al in European population 7-10%, 9 Woo et al in Mongolians 10%, 10 Chanwit Maneenin et al in Northeastern Thai 10.12%, 11 Ajmani et al Nigerians 3.4%, 12 Herker NG et al in African and Maharastrian (Miraj) 1% & 3%.…”
Section: Discussionmentioning
confidence: 79%
“…Incidence of persistence metopic sutures in Indian populations were observed by previous authors as follows, B. V. Murlimanju, 52 (64.1%), 4 Hussain Saheb S 3.2%, 5 Agarwal 2.66%, 6 Das 3.31%, 7 Jit & Shah 5%. 8 Incidence among other population were , Breathnach et al in European population 7-10%, 9 Woo et al in Mongolians 10%, 10 Chanwit Maneenin et al in Northeastern Thai 10.12%, 11 Ajmani et al Nigerians 3.4%, 12 Herker NG et al in African and Maharastrian (Miraj) 1% & 3%.…”
Section: Discussionmentioning
confidence: 79%
“…Infact the studies carried on Indian population have revealed that incidence of metopism in different region of country vary between 2.66-5% [5,6,8] , . Murlimanju observed incidence of metopism in Indian population-64.1% [9].Hussain Saheb S et al reported incidence of metopism in South Indian skulls as 29.6% [10].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of metopic suture varies in different races-4-5% in Yellow races, 7-10% in Europeans and 1% in African skulls [4]. Das et al reported the incidence of metopism in Indian skulls was 27.98% [5] whereas according to agarwall 40.83% skulls showed metopism [6]. Incidence of metopism in Indian skulls were low compared to the Alpine skulls (63.2%) but much higher compared to Australian (1%) and Scottish skulls (9.5%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…If the sutureis not present All the skulls were macroscopically examined and inspected carefully at normafrontalis for the presence or absence of the metopic suture. The method of classification of the metopic sutures is done based on the earlier studies on metopic 13,14 suture. It was considered to be complete when it continued uninterruptedly from the nasion to the bregma.…”
Section: Introductionmentioning
confidence: 99%